2022
DOI: 10.3390/cancers14246244
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Cytogenetic Characterization of Early and Late Relapses in Patients Allografted for Myeloid Neoplasms with a Myelodysplastic Component

Abstract: An improved understanding of relapse kinetics is required to optimize detection and treatment strategies for the post-transplant relapse of myeloid neoplasms. Therefore, we retrospectively analyzed data from 91 patients allografted for MDS (n = 54), AML-MRC (n = 29) and chronic myelomonocytic leukemia (CMML, n = 8), who relapsed after transplant. Patients with early (<12 months, n = 56) and late relapse (>12 months, n = 35) were compared regarding patient-, disease- and transplant-related factors, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…These observations are in line with the analyses of Platte et al, who found cytogenetics, disease risk stratification at diagnosis, and pretransplant strategies to be major determinants for the time of relapse. [37]. Our data regarding timely reconstitution of neutrophils and platelets, rate of acute and chronic GVHD, no additional extra hematologic toxicity, as well as early response and relapse are in line with the results of Garcia et al, who added venetoclax to fludarabin/busulfan and evaluated the combination as feasible and safe [21].…”
Section: Discussionsupporting
confidence: 88%
“…These observations are in line with the analyses of Platte et al, who found cytogenetics, disease risk stratification at diagnosis, and pretransplant strategies to be major determinants for the time of relapse. [37]. Our data regarding timely reconstitution of neutrophils and platelets, rate of acute and chronic GVHD, no additional extra hematologic toxicity, as well as early response and relapse are in line with the results of Garcia et al, who added venetoclax to fludarabin/busulfan and evaluated the combination as feasible and safe [21].…”
Section: Discussionsupporting
confidence: 88%
“…These observations are in line with the analyses of Platte et al, who found cytogenetics, disease risk stratification at diagnosis and pretransplant strategies to be major determinants for the time of relapse. [39]. Our data regarding timely reconstitution of neutrophils and platelets, rate of acute and chronic GVHD, no additional extra hematologic toxicity as well as early response and relapse are in line with the results of Garcia et al who added Venetoclax to Fludarabin/Busulfan and evaluated the combination as feasible and safe [22].…”
Section: Discussionsupporting
confidence: 88%